Nuclear North Korea : regional dynamics, failed policies, and ideas for ending a global stalemate - Yi, Su-hun. (Seoul : Institute for Far Eastern Studies, Kyungnam University Press, 2012)
'North Korea's development of weapons of mass destruction has not only affected regional security, but also caused considerable anxiety at the global level. The authors of Nuclear North Korea explore the whats, whys and hows of the DPRK's nuclear program and offers fresh ideas on how to contain the country's nuclear ambitions.'--P. [4] de la couv.
Includes index.
Keywords: Armes nucleaires -- Coree du Nord; Securite nationale -- Coree du Nord